Improving the efficiency of estrus synchronization in cows (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to determine the effects of biologically active substances and electrical stimulation of the uterus in cows on the effectiveness of estrus synchronization. Materials and Methods: Ninety (n = 90) Kazakh white-headed cows were synchronized with two injections of gonadotropin-releasing hormone on days 0 and 9 and prostaglandin F2α on day 7. The cows were divided into six groups and, during the protocol, treated with biologically active substances (Tetramag, Selevetum, antiseptic-stimulator Dorogov 2 fraction, groups 2, 3, and 4). Cows in groups 5 and 6 were treated with the same substances but additionally had electrical stimulation of the uterus, while cows in group 1 were left untreated and served as a control. Results: The results have shown that on Day 0, no differences were observed in E2 concentrations between the groups. However, on the 10th day, a significant disparity was noted in the E2 level among cows in group 6 compared to groups 2, 3, 4, and the control group. Conversely, no significant differences were observed between groups 5 and 6. Likewise, the fertility rate in cows from group 6 was significantly higher compared to groups 2, 3, 4, and the control group, with no significant differences between groups 5 and 6. Conclusion: It can be concluded that the utilization of electrical stimulation of the uterus and the inclusion of certain biological substances during the estrus synchronization protocol demonstrate a positive effect on the reproductive performance of beef cattle in Kazakhstan.Adv. Vet. Anim. Res., 11(1): 100-106, March 2024http://doi.org/10.5455/javar.2024.k753